Return to play management after concussion in football: recommendations for team physicians - Feddermann-Demont, N.; Straumann, D.; Dvorák, J. (Journal of Sports Sciences, 2014)
A concussion is a rare but potentially serious injury of football players. Thus, an immediate and valid diagnosis, estimate of severity and therapeutic management is required. To summarise the published information on management of concussion with respect to a safe return to play (RTP), a literature search was conducted. Current guidelines on concussion in sports and significant studies on concussion in football were analysed. After concussion, management and RTP decision should remain in the area of clinical judgement on an individualised basis according to the current international guidelines. If a concussion is suspected, the player should not be allowed to RTP the same day. The RTP programme should follow a gradual step-wise procedure. A concussed player should not RTP unless he/she is asymptomatic and the neurological and neuropsychological examinations are normal. Untimely RTP bears an increased risk of sustaining another more severe brain injury and repetitive brain injury of long-term sequelae. In football, the management of concussion should primarily follow the recommendations proposed by the Concussion in Sports Group. Information and education of players and their medical and coaching team help to protect the players` health. Future studies on concussion should include validated and detailed information on RTP protocols.